Assessment and Comparison of Oropharyngeal Airway Dimensions in Skeletal Class II Cases Treated With Forsus FRD and Twin Block Appliances - Shetty, Kaushik; K., Saidath; Shetty, Akhil; Ravi, M. S.; Shashidhar, Keerthan; A., Anushree (Journal of Health and Allied Sciences NU, 2017)
Aims: To assess the changes in the oropharyngeal airway (OAW) dimensions in individuals with retrognathic mandible treated with Forsus FRD and Twin Block appliance to correct the skeletal Class II mal relationship.Methodology: 40 individuals, with Class II skeletal pattern were selected as per inclusion criteria. Pre-treatment lateral cephalograms and hand wrist radiographs were obtained and analyzed. Group 1 with 20 individuals were treated with Forsus FRD and Group 2 with 20 individuals were treated with conventional Twin Block Appliance. Post treatment records were taken after the Class I molar relationship had been obtained. Pre and post treatment cephalograms were compared and analyzed. The data obtained was statistically evaluated using paired t test and unpaired t test.Results: On comparison of pre-treatment and post-treatment cephalograms, increase in Oropharyngeal Airway (OAW) measurements, such as Superior posterior airway space (SPAS), Middle airway space (MAS) and Inferior airway space (IAS) was very highly significant.Conclusion: Our results suggest the existence of a relationship between functional-orthopaedic treatment and increases in OAW dimensions in skeletal Class II growing subjects.
Keywords: Skeletal malocclusions; airway assessment; myofunctional appliance; fixed functional appliance.